1999
DOI: 10.1016/s0378-1097(99)00258-x
|View full text |Cite
|
Sign up to set email alerts
|

Restriction fragment length polymorphism analysis of the flaA gene of Campylobacter jejuni for subtyping human, animal and poultry isolates

Abstract: 233 strains of Campylobacter jejuni were subtyped by PCR-RFLP analysis of the flagellin (flaA) gene by double digestion with EcoRI and PstI (EP flaA-profiling). The strains represented a variety of common Penner heat stable (HS) serotypes and comprised isolates of human, bovine, ovine, chicken and canine origin. FlaA amplicons were obtained directly from DNA in cell lysates of most strains. RFLP analysis showed considerable allelic variation and nine EP flaA-types were identified of which the most common were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
1
14
0
1
Order By: Relevance
“…With multilocus enzyme electrophoresis analysis, a suitable method for evaluating population genetics of other bacteria, no subgroups of human and animal C. jejuni strains were identified (1). With other typing methods, such as PCR-RFLP analysis of flaA genes, considerable allelic variation of this gene in human and animal strains was observed (20). Also, RAPD analysis could not identify distinct subgroups (13).…”
Section: Discussionmentioning
confidence: 98%
“…With multilocus enzyme electrophoresis analysis, a suitable method for evaluating population genetics of other bacteria, no subgroups of human and animal C. jejuni strains were identified (1). With other typing methods, such as PCR-RFLP analysis of flaA genes, considerable allelic variation of this gene in human and animal strains was observed (20). Also, RAPD analysis could not identify distinct subgroups (13).…”
Section: Discussionmentioning
confidence: 98%
“…Pulsed-field gel electrophoresis using three different restriction enzymes also identified clones found in cattle, poultry, and humans (19). However, restriction fragment length polymorphism analysis of the flaA gene using EcoRI and PstI showed that most flaA types were associated with several hosts (20).…”
Section: Discussionmentioning
confidence: 99%
“…Studying the transmission of antimicrobial resistance from animals to man is difficult, especially from poultry to man, because the chain of transmission is often complex. However, several studies have shown that food animals can serve as an important source of infection in humans and that the same sero-and genotypes can be isolated from humans and food animals [37,38,40]. Since human-to-human transmission of C. jejuni/coli is rare, patients infected with resistant Campylobacter are not an important source of resistant Campylobacter for other humans.…”
Section: Discussionmentioning
confidence: 99%